Guidelines improve patient outcomes in specialised mental health care: A systematic review and meta‐analysis. (5th July 2021) - Setkowski, Kim; Boogert, Kelly; Hoogendoorn, Adriaan W.; Gilissen, Renske; van Balkom, Anton J. L. M.
Abstract: Objective: The uptake of evidence‐based guideline recommendations appears to be challenging. In the midst of the discussion on how to overcome these barriers, the question of whether the use of guidelines leads to improved patient outcomes threatens to be overlooked. This study examined the effectiveness of evidence‐based guidelines for all psychiatric disorders on patient health outcomes in specialist mental health care. All types of evidence‐based guidelines, such as psychological and medication‐focused guidelines, were eligible for inclusion. Provider performance was measured as a secondary outcome. Time to remission when treated with the guidelines was also examined. Method: Six databases were searched until 10 August 2020. Studies were selected, and data were extracted independently according to the PRISMA guidelines. Random effects meta‐analyses were used to pool estimates across studies. Risk of bias was assessed according to the Cochrane Effective Practice and Organization of Care Review Group criteria. PROSPERO:CRD42020171311. Results: The meta‐analysis included 18 studies (N = 5380). Guidelines showed a positive significant effect size on the severity of psychopathological symptoms at the patient level when compared to treatment‐as‐usual (TAU) ( d = 0.29, 95%‐CI = (0.19, 0.40), p < 0.001). Removal of a potential outlier gave globally the same results with Cohen's d = 0.26. Time to remission was shorter in the guideline treatment compared with TAU (HR = 1.54, 95%‐CI = (1.29, 1.84), p = 0.001, n = 3). Conclusions: Patients cared for with guideline‐adherent treatments improve to a greater degree and more quickly than patients treated with TAU. Knowledge on the mechanisms of change during guideline‐adherent treatment needs to be developed further such that we can provide the best possible treatment to patients in routine care.